The success factors of public consultation in the establishment of a biosphere reserve - evidence from Tasik Chini - Ahmad, Habibah; Idris, Mushrifah; Jusoh, Hamzah; Toriman, Mohd Ekhwan; Buang, Amiah @ Amriah; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
Biosphere Reserves are the UNESCO's programmes to achieve sustainable development. One important prerequisite in the nomination of a new Biosphere Reserve site is the implementation of a public consultation with all stakeholders including the local community. This article analyses the stakeholder perception during a public consultation exercise conducted for the nomination of Tasik Chini as a Biosphere Reserve. The methodology involved a focus group discussion and a perception survey of 53 adults and 18 youths who participated in a public awareness programme held in 2008. The results of the analysis identified four main success factors of the public consultation programme: (1) an in situ public awareness programme cleverly and interestingly designed to adequately inform the stakeholders on the essence, elements and objectives of a Biosphere Reserve (BR); (2) the care taken by the organisers of the awareness and public consultation programme to get every segment of the stakeholders invited, represented and consulted; (3) the content of the awareness campaign which focussed directly on the benefits of the BR - the 'what's in it' – for the various stakeholders involved; and (4) the sequencing of the public consultation activities – where dissemination of knowledge and awareness creation preceded opinion gathering - had managed to convert an initial 70% ignorance to an eventual 100% acceptance of the BR project. In conclusion, it is essential to note that without sustained involvement of the local stakeholders the future of a BR will more likely than not be in peril.